Epidemiological Study on Bronchial Asthma at Shaheed Suhrawardy Medical College Hospital, Dhaka - Barua, Uttam Kumar; Saha, Santosh Kumar; Ghosh, Dilip Kumar; Ruble, Md. Mesbahul Karim (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: In Bangladesh more than 100 million people are suffering from cough and shortness of breath. Still people are getting unplanned treatment and taking unscientific, indigenous and sometimes harmful products to get relief. Objective: The present study was conducted to estimate the prevalence of different types of bronchial asthma in Shaheed Suhrawardy Medical College Hospital. Methodology: One hundred patients from respiratory medicine out patient department were included in this study using a well designed questionnaire, clinical examination by physician which was carried out from January, 2012 to June, 2012. The key questions were related to the type of asthma, family history, presence of atopic dermatitis and diabetes, information on smoking and alcoholic habits, domestic cooking fuel used, dwelling area, age, religion, socioeconomic status and age of onset of disease. Result: Out of 100 subjects surveyed, 42 were females and 58 were males. The type of asthma is distributed as cough-variant-asthma (8%), intermittent asthma (52%), persistent asthma (16%), seasonal asthma (22%) and occupational asthma (2%). Regarding family history, 26% showed genetic predisposition irrespective of sex. Among asthmatics, 6% were having atopic dermatitis. Forty percent were smokers, 5% were alcoholics and 28% were with diabetics. Advancing age, usual residence in urban area and lower socio-economic status were associated with significantly higher odds of having asthma. Conclusion: It showed that cough- variant-asthma, diabetes and smoking habit increase the incidence of asthma attacks. DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20759 J Shaheed Suhrawardy Med Coll, 2013;5(2):77-80